From the waiting room to the bed: Observation of families on the Intensive Care Unit (Research, Society and Development, 2021)
Objective: to evaluate the observations of family members of patients admitted to the adult Intensive Care Unit in relation to the environment and the care provided by professionals. Methodology: Descriptive, qualitative study, carried out from the pre-test of a methodological study, of cross-cultural adaptation of the instrument Family Satisfaction in the Intensive Care Units - 24 for Brazilian Portuguese. 46 family members participated in two hospitals in Brazil. Data were collected through semi-structured interviews and thematic analysis was applied. Results: Two categories were elaborated: “observations of family members about the waiting room” and “observations of family members during the visit to the ICU”. Family members perceive the waiting room as an uncomfortable place and highlighted the professionalism and quality of care developed by the team, however, they identified the need to reduce ambient noise. Final considerations: the highlighted observations show that the family members recognize the professionals' skills and demonstrate satisfaction with the quality of the care provided and the attention received. In addition, they identify the need to implement improvements to favor the recovery of patients.